Clinical outcomes of a CT protocol for simultaneous examination of the aorta and coronary artery in patients with aortic aneurysm - Kim, Hoyoung; Kim, Jihoon; Choe, Yeon Hyeon; Kim, Sung Mok (Frontiers in Cardiovascular Medicine, 2023)
Objectives In patients with aortic aneurysm (AA), coronary artery disease (CAD) increases the risk of perioperative complications and even asymptomatic CAD is associated with adverse clinical outcomes. We aimed to compare coronary-aorta CT (CACT) with thoracoabdominal CT angiography (Aorta CT) for CAD management and clinical outcomes in these patients. Methods We enrolled 479 patients undergoing CACT and 693 patients undergoing Aorta CT as an initial CT scan for AA. The primary outcome was a composite of all-cause death or myocardial infarction (MI) at 3 years after CT. The secondary outcomes were subsequent CAD management and invasive coronary angiography (CAG). Results After index CT scan, the CACT group had a significantly higher rate of coronary revascularization compared with the Aorta CT group (10.7% vs. 3.8%, p < 0.001) but a lower probability of diagnostic CAG among total invasive CAG (32% vs. 55%, p < 0.001). At 3 months after the CT scan, the prescription rates of statins (65.8% vs. 44.6%, p < 0.001) and antiplatelet agents (57.6% vs. 43.9%, p < 0.001) were higher in the CACT group. During follow-up, the CACT group had a significantly lower incidence of the composite outcome of all-cause death or MI (adjusted HR 1.72, 95% CI 1.07–2.78, p = 0.027) than the Aorta CT group. Conclusion Among patients with AA, CACT was associated with a higher rate of subsequent CAD management and a lower risk of all-cause death or MI compared to Aorta CT. When evaluating with AA using CT, simultaneous coronary and aortic evaluation using CACT would be recommended over Aorta CT.